2023
DOI: 10.1021/acs.energyfuels.3c00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pressure and Depressurization Rate of Dissolved CO2 on the Foaming Characteristics of Crude Oil

Abstract: With the CO 2 flooding technique implemented, much CO 2 gas is dissolved in the produced fluid. A large amount of CO 2 escapes from crude oil due to continual depressurization in the surface pipeline system, leading to massive foam. In this paper, the effects of dissolved-CO 2 pressure and depressurization rate on foaming characteristics were investigated by depressurization. To explore the mechanism in depth, CO 2 solubility and interfacial characteristics were considered. The results indicated that foamabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This relationship between CO 2 flow rate and HLT is significant because it directly impacts the stability and performance of CO 2 foam in EOR applications. Sheng et al reported that the depressurization rate negatively affects CO 2 foam stability, with foam stability decreasing as the rate increases . Similarly, Yan and Zhang highlighted the importance of foam stability, as measured by HLT, in reducing foam mobility within the porous media of oil reservoirs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship between CO 2 flow rate and HLT is significant because it directly impacts the stability and performance of CO 2 foam in EOR applications. Sheng et al reported that the depressurization rate negatively affects CO 2 foam stability, with foam stability decreasing as the rate increases . Similarly, Yan and Zhang highlighted the importance of foam stability, as measured by HLT, in reducing foam mobility within the porous media of oil reservoirs .…”
Section: Resultsmentioning
confidence: 99%
“…Other factors influencing foam stability include the presence of oil itself, injection velocity, and rock formation characteristics . The interplay between various parameters like pressure, depressurization rate, CO 2 solubility in the oil, and interfacial properties significantly impacts the effectiveness of CO 2 foaming in crude oil systems . Optimizing injection rate, foam quality, and the CO 2 /N 2 ratio is crucial for achieving maximum oil recovery and stable foam .…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the research work on stimulus-responsive WLM-CO 2 foam has mainly focused on temperature, concentration, pressure, and response optimization. 25 In explorations of the influence of crude oil on WLMs (mostly with a single hydrocarbon representing crude oil), a gap exists between the construction of the crude oil system and the actual situation. For research on the stimulus-responsive WLM-CO 2 foam system to become systematic, the interaction between crude oil and CO 2 foam must be further explored by dividing crude oil into four components: 26,27 saturated hydrocarbons, aromatic hydrocarbons, resin, and asphaltene.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At this stage, the research work on stimulus-responsive WLM-CO 2 foam has mainly focused on temperature, concentration, pressure, and response optimization . In explorations of the influence of crude oil on WLMs (mostly with a single hydrocarbon representing crude oil), a gap exists between the construction of the crude oil system and the actual situation.…”
Section: Introductionmentioning
confidence: 99%